Enhancing mathematical communication skills through cooperative learning model-based worksheets of talking stick type - Kurniawati, Eka Fitri; Sudiana, Ria (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study addresses the deficiency in students' mathematical communication skills attributed to teaching materials that do not effectively contribute to their development. The unappealing presentation of teaching materials leads to student boredom during learning activities and the adoption of inappropriate learning models. Therefore, enhancing communication skills through worksheets (LKPD) based on the cooperative talking stick model is essential. This research is research and development (R&D) using the research design of the development model of Borg and Gall (1983) with ten stages. However, in this study, only nine stages are considered, including 1) potential and problems, 2) data collection, 3) product design, 4) product validation, 5) product revision, 6) initial trials, 7) revisions, 8) usage trials, 9) Final revision, because this model has high validation that has been tested by several experts and produces an effective product. The research subjects comprised 35 ninth-grade students for the small-scale trials and 70 eighth-grade students for the large-scale trials. Data collection techniques in the form of questionnaires, tests, and documentation. The results of the feasibility test conducted by material experts, considering content, presentation, and language feasibility, yielded a score of 83.5%, and the results of media experts with aspects of model size, cover design, content design, component suitability obtained a value of 86.8% so that very feasible criteria were obtained. Based on teacher responses, the practicality test results yielded a score of 86.67%, and the results of the student's response obtained a value of 82.55%, so the response obtained very practical criteria. The effectiveness test results, employing N-Gain to measure student improvement after using the developed products to enhance mathematical communication skills, yielded 61.14%, indicating moderate effectiveness. Based on this, the products developed meet the criteria of feasibility, practicality, and effectiveness in the learning process.